FASILITASI PERDAGANGAN, KINERJA EKSPOR, DAN KETIMPANGAN PENDAPATAN DI NEGARA-NEGARA RCEP - Raiyatu Imadidin; Dominicus Savio Priyarsono; Widyastutik Widyastutik (JURNAL EKONOMI DAN KEBIJAKAN PEMBANGUNAN, 2017)
The growth of global economic integration has added pressure for countries to reduce trade cost to make trades more profitable and to encourage their further development. As tariffs have progressively fallen, efforts in trimming trade costs have focused increasingly on non tariff measures, which have a detrimental impact on the free flow of international trade, as such trade facilitation is considered an important complement to trade liberalization efforts aimed at fostering economic integration. Trade is expected to increase overall national income. The increase in national income can be used to improve welfare by increasing household income which translates into inequality alleviation. Regional Comprehensive Economic Partnership (RCEP) is a form of cooperation between 16 countries in the Association of Southeast Asian Nation and other major trading partner countries. This study uses a simultaneous panel method to identify the trade facilitation, export performance, and income inequality by using 12 countries in the RCEP region during 2011-2015 period. The results show that the advantages of trade facilitation in RCEP associated with export performance to decrease inequality in RCEP region and RCEP developing countries, but increase increase in RCEP developed countries. Keywords: Export performance, Inequality, RCEP, Trade facilitation